Evaluation of The Minimum Wage Determination System Indonesian Workers Based on Comparison Policy - Syirfan, Muhammad Addi; Kamalludin, Iqbal (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2022)
This study was motivated by an increase in the average provincial minimum wage in 2022 across Indonesia by 1.09%. The percentage increase is considered not proportional to the increase in the price of goods to meet the needs of workers and their families. When compared to the average increase in the minimum wage in previous years, the provision of UMP increases in 2022 is relatively low. This research uses normative legal research methods with secondary data collection techniques. This research aims to educate a wide audience on the system of determining the minimum wage of Indonesian workers based on a comparison of wage policies. In addition, this study will provide an overview of the comparison of the wage system through the method of Government Regulation  78 of 2015 with Government Regulation 36 of 2021. The results of this study showed that the minimum wage determination system with the PP 78 method in 2015 prioritizes workers and their welfare. In addition, the government regulation uses democratic principles and considers the standard of living needs (KHL) in determining its minimum wage. Meanwhile, the minimum wage determination system using the PP 36 of 2021 method uses a established formula. The formula uses the upper median and lower median references in measuring the rate of salary increases of workers in Indonesia.